2012
DOI: 10.5209/rev_sjop.2012.v15.n2.38883
|View full text |Cite
|
Sign up to set email alerts
|

About the Dark and Bright Sides of Self-efficacy: Workaholism and Work Engagement

Abstract: Taking the Resources-Experiences-Demands Model (RED Model)by Salanova and colleagues as our starting point, we tested how work self-efficacy relates positively to negative (i.e., work overload and work-family conflict) and positive outcomes (i.e., job satisfaction and organizational commitment), through the mediating role of workaholism (health impairment process) and work engagement (motivational process). In a sample of 386 administrative staff from a Spanish University (65% women), Structural Equation Model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(57 citation statements)
references
References 69 publications
3
44
1
2
Order By: Relevance
“…In line with this view, prior empirical studies have shown that workaholism is related to negative outcomes for employees, such as lower job satisfaction (e.g. Del Líbano et al, 2012;van Beek et al, 2014), lower life satisfaction (Bonebright et al, 2000), and poorer social relationships outside their work (Schaufeli et al, 2008b). Workaholic employees have also been found to be less happy (Schaufeli et al, 2009b), to suffer more from health complaints, and to report lower levels of self-perceived health (e.g.…”
Section: Workaholism and Work Engagementmentioning
confidence: 77%
“…In line with this view, prior empirical studies have shown that workaholism is related to negative outcomes for employees, such as lower job satisfaction (e.g. Del Líbano et al, 2012;van Beek et al, 2014), lower life satisfaction (Bonebright et al, 2000), and poorer social relationships outside their work (Schaufeli et al, 2008b). Workaholic employees have also been found to be less happy (Schaufeli et al, 2009b), to suffer more from health complaints, and to report lower levels of self-perceived health (e.g.…”
Section: Workaholism and Work Engagementmentioning
confidence: 77%
“…The group of attributes that received most attention was self-efficacy, resilience and personal resources; in other words, the positive perceptions that individuals hold of their personal strength and belief in their own ability, which featured in 10 studies. 111,119,141,215,228,229,265,[276][277][278] These studies show a positive association between these factors and engagement. For instance, Ouweneel et al 265 surveyed individuals at two time points and found that personal resources at time 1 were associated with engagement at time 2.…”
Section: Individual Psychological Statesmentioning
confidence: 83%
“…72,141,168,166,167,173 All found that engagement was positively associated with organisational commitment. Wefald et al 101 examined which dimensions and measures of engagement were most associated with organisational commitment.…”
Section: Organisational Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have found that workaholics typically endure negative consequences in several parts of their lives, including work stress (Aziz & Zickar, ), burnout (Schaufeli et al., ), poor physical and mental well‐being (Taris, Schaufeli, & Verhoeven, ), and work–life imbalance (Clark et al., ). Given that workaholics think about work even when not working and feel they must always be working, they do not have enough recovery time during nonwork hours and usually lack social relationships (Clark et al., ; Del Libano, Llorens, Salanova, & Schaufeli, ; van Wijhe et al., ). Additionally, Clark et al.…”
Section: Workaholism Overviewmentioning
confidence: 99%